Copyright Protection Of Wayang Kulit Digital Transformation - Ketut Sudadnyana; Putu Ayu Sriasih Wesna; I Wayan Rideng (Jurnal Smart Hukum (JSH), 2026)
This study investigates copyright protection in the digital transformation of Wayang Kulit as a traditional cultural expression within the Indonesian legal system. It specifically addresses the normative ambiguity surrounding the recognition of transformed works under Article 40(1)(n) of the Copyright Law. Employing a normative legal research design with statutory and conceptual approaches, the study critically examines whether digital reinterpretations such as animation, digital illustration, and interactive media, qualify as independently protected works. The analysis demonstrates that, although the law formally acknowledges transformative creations, it fails to provide clear criteria regarding the threshold of originality and the extent of permissible modification. This regulatory gap generates legal uncertainty in determining authorship, ownership, and the scope of protection, particularly when communal cultural elements intersect with individual creativity. The novelty of this research lies in its focused examination of Wayang Kulit as an intangible cultural heritage undergoing digital recontextualization, integrating doctrinal legal analysis with cultural considerations. The findings suggest that without clearer interpretative guidance and regulatory refinement, copyright law risks inadequately protecting both traditional cultural values and contemporary creative contributions. Accordingly, this study concludes that a more adaptive and coherent legal framework is required to balance communal rights and individual interests in the digital era. Future research should explore comparative legal models and develop context-sensitive approaches to governing cultural transformations in digital environments.